Experiences of weight-related stigma among low-income rural women of higher weights from the midwestern United States - Katherine Hughes; Andrea E. Bombak; Samuel Ankomah (Qualitative Research in Medicine & Healthcare, 2019)
Weight-related stigma and stereotypes are widespread. Despite established research highlighting the disproportionate disparities rural individuals face, studies focusing on women in rural and low-income environments are underrepresented in the literature. The current study addressed these gaps in the literature using 25 in-depth interviews, which were analyzed using interpretive phenomenological procedures. The research questions were: i) what are low income rural women of higher weights’ understandings and experiences of weight stigma in healthcare? and ii) to what extent do their experiences of stigma affect or do not affect their healthcare-related behaviors? Sixteen women in the study experienced weight-related stigma in healthcare. Many delayed their care while others felt their care was essentially denied. Findings indicate that more can be done to address weight-related stigma.